Consumer Behaviour at the Generic Level: Theoretical Perspectives - Rahmat Hidayat (Buletin Psikologi, 2014)
Suppose you had unexpectedly received some money, for instance a gift or a lottery prize. What would you like to do with the money? Why the action you chose to do is of much importance to you? What would you like to achieve by that action? This is a simple illustration of the generic level of consumer decision making, henceforth the generic level. It is important to note that neither money nor unexpec- tedness defines the generic level. Although there are plenty of examples of receiving a windfall, gifts and lottery prizes being two of them, the generic level also concerns situations when expectations rule. For example, people may expect to receive a bumper bonus, an extra profit, a tax return, gain excessive money from a pre- vious budget, or even to inherit some valuable assets from their beloved parents. To a certain degree, people in such situations must ponder of the different ways to utilize the money. The defining features of the generic level concern the mental processes of decision making in which an individual is trying to allocate a consumer resource into different cate- gories of activities (Van Veldhoven & Groenland, 1993).